Clinical-Psychological Aspects Involved in Gynecological Surgery: Description of Peri-Operative Psychopathological Symptoms and Illness Behavior - Sara Guidotti; Carlo Pruneti; Simona Mortilla; Giuseppe Masellis; Chiara Caramuscio (International Journal of Psychological Research, 2023)
Background. Within the current literature concerning the gynecological surgery, there are only a few studies that focus on the psychological aspects that characterize the peri-operative period. In this research, the psychopathological symptoms and the illness behavior were assessed in order to confirm previous results about clinical variables such as the type and method of intervention, as well as psychological aspects regarding the positive anamnesis for mental disorders. Moreover, other factors including the desire for maternity and previous surgical interventions and pregnancies were also investigated. Methods. In this observational research, 58 women (age = 41.5±8.8), that undergone gynecological surgery (conservative and non-conservative) for benign pathologies, were consecutively recruited. Information on psychopathological symptoms was collected 15 days (T0) and one day before surgery (T1), and at the time of discharge (T2) through the Symptom Questionnaire (SQ). At T2, the Illness Behavior Questionnaire (IBQ) was also administered. Results. The descriptive analyzes conducted on the total sample demonstrated that while anxious activation and irritable mood decrease from T0 to T1, somatizations and depression mood increase between T1 and T2. Moreover, the comparisons between groups, dividing the sample according to the clinical-medical and psychological variables, highlighted that the type and modality of the intervention, as well as a positive history for the presence of psychological disorders, the desire for maternity, and previous surgical interventions and pregnancies, can influence the course of psychopathological symptoms. Conclusion. This study highlights the need to include a clinical-psychological evaluation and to pay attention to specific clinical variables regarding women that are undergoing a conservative or non-conservative gynecological surgery. Considering the psychological impact of these type of interventions, the clinical history of these women, as well as their fears and desires, could facilitate a better management of the patients in terms of well-being, adherence to treatment, and recovery